Psychiatric Disturbances In Chronic Renal Failure Patients Undergoing Maintenance Hemodialysis: A Cross Sectional Observational Study - Dr. Harish Basera , Dr. K. C Pant , Dr. Js Bisht (Drugs and Cell Therapies in Hematology, 2021)
Background: End-Stage Renal Disease (Esrd) Is The Most Severe Stage Of Kidney Failure, In Which Kidney Function Has Been Lost Permanently. Because Of Increased Life Expectancy And The Development Of Lifestyle Disorders Such As Diabetes And Hypertension, The Incidence Of Esrd Has Grown In Recent Years. Renal Transplantation Is The Best Treatment Option For This Condition, Followed By Hemodialysis. The Majority Of Patients Are Forced To Use Dialysis Due To The Scarcity Of Transplants Compared To The Need. Hemodialysis (Hd), Which Is Usually Done In A Tertiary Health Care Setting, Is Still The Most Widely Used Modality On The Planet. Objectives: 1.To Assess Prevalence Of Depression And Anxiety In Esrd Patients On Chronic Hemodialysis. 2. To Assess Factors Causing Depression And Anxiety In Esrd Patients On Chronic Hemodialysis. Methods: At A Tertiary Healthcare Centre In Central India, A Cross-Sectional Observational Study Was Done. The Beck Depression And Anxiety Inventory Were Used To Examine Patients With Chronic Renal Failure Who Had Been On Maintenance Dialysis For More Than 6 Months For Depression And Anxiety. To Evaluate The Data, Statistical Tests Were Used. Results: The Intensity Of Depression Increased As The Length Of Dialysis Increased, Although The Degree Of Anxiety Reduced. Patients With Esrd Must Have Hemodialysis On A Regular Basis, As Well As Make Dietary, Hydration, And Medicine Consumption Modifications. Conclusion: Many Hd Patients Have Mental Difficulties, Including Depression And Anxiety, In Addition To Physical Disabilities. Depression Is More Common Among Dialysis Patients Than In The General Population, And It Is Linked To A Poor Prognosis. The Prognosis In This Demographic Group Will Be Improved If Risk Factors Related With Psychiatric Symptoms Are Identified Early.